PENGARUH TINGKAT PENGANGGURAN, PERTUMBUHAN EKONOMI, TINGKAT PENDIDIKAN DAN UMR TERHADAP TINGKAT KEMISKINAN KABUPATEN/KOTA PROVINSI BALI - Hadi, Ni Made Lita Prilia; Yasa, I Gusti Wayan Murjana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The increasing number people living below the poverty line is due to the high disparity between regions. The purpose this study to analyze and determine effect of unemployment rate, economic growth, education level and UMR simultaneously and partially on poverty level in districts/cities of Bali Province and the variables have a dominant influence on the poverty level in Bali Province. This study uses panel data for 2015-2019 period with multiple linear regression analysis techniques, coefficient determination analysis and descriptive statistical analysis. The results of the study show 1) Unemployment rate, economic growth, education level and UMR simultaneously affect the poverty rate in the districts/cities of Bali Province. 2) Unemployment rate partially has positive significant effect on poverty level, economic growth partially has an negative insignificant effect on poverty level, the education level partially has a negative significant effect on poverty level, while UMR partially has a positive significant effect on poverty level in districts/cities Bali province. 3) The most dominant variable on poverty rate is unemployment rate in the districts/cities of Bali Province. Keywords : unemployment rate; economic growth ; education level; regional minimum wage and poverty rate.